Komparasi Penyelesaian Perkara Pidana Kejahatan Genosida yang Terjadi di Rwanda dan Myanmar Ditinjau Dari Perspektif Hukum Pidana Internasional - Riski Wahyudi, Anak Agung Ngurah; Budiana, I Nyoman (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
This study aims (1) to analyze and find out the efforts to resolve genocide disputes from the perspective of international criminal law, (2) to determine the comparison of resolving genocide disputes that occurred in Rwanda and Myanmar. This type of research uses normative legal research, namely literature study, rules and literature related to genocide, and uses an argumentative descriptive approach. The results of this study explain the efforts and comparisons of resolving genocide disputes that occurred in Rwanda and Myanmar from the perspective of international criminal law. Genocide is an international crime that aims to eliminate ethnicity, ethnicity, race and religion in a systematic and structured manner. Efforts to resolve disputes are carried out in an international criminal manner and are handled by the International Criminal Court. The International Criminal Court is the highest judicial institution, and has the authority to handle international cases. comparative law is a method of investigation with the aim of obtaining deeper knowledge about certain legal materials. Comparative law is not a set of rules and legal principles and is not a branch of law, but is a technique for dealing with foreign legal elements from a legal problem.Â Court. The International Criminal Court is the highest judicial institution, and has the authority to handle international cases